Elementary Principals and Their School Districts in Three Categories of Ruralness - Janet L. Pladson; Donald K. Lemon (Journal of Research in Rural Education, 1982)
This paper describes a model of relative ruralness for rural states and applies it to North Dakota.From the model, descriptions of the principals and the districts were generated. Comparisons between principals and districts by ruralness are made. Further research is suggested.